Entrapment of water by subunit c of ATP synthase - McGeoch, Julie E.M (The Royal Society, 2007)
We consider an ancient protein, and water as a smooth surface, and show that the interaction of the two allows the protein to change its hydrogen bonding to encapsulate the water. This property could have made a three-dimensional microenvironment, 3–4 Gyr ago, for the evolution of subsequent complex water-based chemistry. Proteolipid, subunit c of ATP synthase, when presented with a water surface, changes its hydrogen bonding from an α-helix to β-sheet-like configuration and moves away from its previous association with lipid to interact with water surface molecules. Protein sheets with an intra-sheet backbone spacing of 3.7 Å and inter-sheet spacing of 6.0 Å hydrogen bond into long ribbons or continuous surfaces to completely encapsulate a water droplet. The resulting morphology is a spherical vesicle or a hexagonal crystal of water ice, encased by a skin of subunit c. Electron diffraction shows the crystals to be highly ordered and compressed and the protein skin to resemble β-sheets. The protein skin can retain the entrapped water over a temperature rise from 123 to 223 K at 1×10(−4) Pa, whereas free water starts to sublime significantly at 153 K.